A survey of theological seminary libraries belonging to Asia Graduate School of Theology (AGST) with implications for interlibrary loan policy - Capuno, Mary Ruth A.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
The term interlibrary loan encompasses both borrowing and lending - the requesting of materials and the sending of materials, including provision of reproductions. This study is about the theological seminary libraries belonging to Asia Graduate School of Theology (AGST) Consortium. A survey questionnaire was used to obtain data about the collection of the library as well as the services they give to their patrons. The data collected from the questionnaire was compiled, tabulated and analyzed.
According to the findings of the survey it is clear that a formal written interlibrary loan policy would be beneficial for the AGST Consortium. The findings show that they have been practicing an interlibrary loan not only within the AGST Consortium but also with other libraries outside the Consortium. While this has been helpful, a formal policy would greatly enhance their services to their patrons. Lending and borrowing of materials would be more organized because of shared union lists of books and serials, and a standard procedure among others.
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman.
Vita
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Asia Graduate School of Theology; Interlibrary loans -- Policy statements; Theological seminary libraries -- Philippines